Outer membrane protein NmpC of Escherichia coli: pore-forming properties in black lipid bilayers. - Hindahl, M S (1984)
The purified NmpC outer membrane protein from Escherichia coli, when incorporated into planar lipid bilayers, gave rise to channels with a single-channel conductance of 1.8 nS in 1 M KCl. This suggests that the NmpC protein is a porin.